Person-job fit and innovative behavior in new R&D institutions: the mediating effects of self-efficacy and job involvement on business decision-making - Jiang, Ming; Geng, Feng; Zhang, Dechong; Meng, Chao; Li, Shaopeng; Peng, Yajie (Frontiers in Psychology, 2025)
In recent years, new R&D institutions have emerged in China, distinguished from traditional research entities by their unique structure and objectives. This study explores the impact of person-job fit on the innovative behavior of 334 researchers within these institutions. Through hierarchical regression analysis and bootstrap methods, we find that person-job fit significantly enhances innovative behavior. Furthermore, self-efficacy and job involvement partially mediate this relationship. These findings offer practical implications for managers seeking to foster innovation by aligning employees’ roles with their skills and motivations, thereby improving organizational effectiveness and supporting strategic business decisions.